Implementation of the International Community Service Program (KKNI) in Strengthening Literacy and Character Development of Indonesian Diaspora Children in Malaysia - Muhammad Fikri Almajid Munthe; Iin Natasya Divana Ginting; Yummy Jumianti Marsa; Rusi Ulfa Hasanah; Siti Aisyah (Civiliza Publishing, 2026)
This study aims to analyze the implementation of the International Community Service Program (KKNI) of Universitas Islam Negeri Sumatera Utara in strengthening literacy and character development among Indonesian diaspora children at Sanggar Belajar Gumut, Selangor, Malaysia. The study employed a descriptive qualitative approach using participatory observation, in-depth interviews, and field documentation methods. The findings indicate that the KKNI program was able to improve children’s ability to read and write the Qur’an, recognize Latin letters and numbers, and foster discipline and responsibility through creative literacy activities, savings simulations, and moral guidance. In addition to cognitive impacts, the program also strengthened the moral values, empathy, and social cooperation of diaspora children. For the participating university students, the KKNI program became a transformative experience that developed empathy, leadership, and cross-cultural communication skills. These findings reinforce the concepts of Community-Based Education and Service Learning, showing that community-based and experiential learning can serve as effective means of shaping character and social spirituality. This study recommends establishing a sustainable partnership between Universitas Islam Negeri Sumatera Utara and Sanggar Belajar Gumut as a model of international community service grounded in Islamic and humanitarian values.